Universal Maqasid al-Shari`ah and their modern application: towards ensuring a peaceful and secured environment - Shihan, Mohammad; Zaroum, AbdulHamid Mohamed Ali; Amanullah, Muhammad (Al-Hikmah Research and Publication Centre, 2021)
The maqasid theory is a popular trend in Islamic legal theories. Contemporary scholars view it as a valid method of interpreting the revealed text and as a valuable instrument for solving contemporary issues because it helps reform Islamic thought and civilization. Indeed, the idea of maqasid al-Shari'ah has been widely studied and expanded by modern scholars of Islamic legal theory. Chiefly, Ibn Ashur and contemporary Maqasid scholars renewed the scholarly discourse and ensured its proliferation and wide acceptance in legal studies. It has emerged as a new science that connects with all other legal disciplines. Thus, scholars firmly assert that the magasid al-Shari'ah constitute the most important intellectual means and methodologies for Islamic reform today. Consequently, the researchers aim to examine the modern discourse of Maqasid al-Shari'ah and the latest developments beyond the universal Maqasid. Mainly, the researchers scrutinize the two objectives namely the preservation of the environment via the protection of life and wealth. Accordingly, this article follows the qualitative method of data collection and analysis. Among the findings of the research is that the latest developments of Maqasid al-Shari'ah, open the door of ijtihad widely to create ample areas for jurists to regulate the affairs of the Muslim ummah. Further, the maqasid al-Shari'ah do not reflect only the objectives of Islamic law; their role goes beyond and is used to formulate basic principles and values related to global peace and human welfare. Hence, they have greatly contributed to the revival of Islamic thought and have opened a wider space for the application of Islamic law pertaining to peaceful environment.